2021
DOI: 10.3390/nu13051507
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet in a School Population in the Principality of Asturias (Spain): Relationship with Physical Activity and Body Weight

Abstract: The Mediterranean diet (MD), despite its multiple benefits, presents low levels of adherence among children. Moreover, childhood is a key stage in the acquisition of healthy habits. The aim of this study was to describe adherence to MD in school-age children from Asturias, Spain, and to evaluate the association with weight status and several lifestyle behaviors. A cross-sectional study was conducted on 309 children aged between 8 and 13 years old. The level of adherence to MD was evaluated through the KIDMED q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(79 reference statements)
1
5
1
Order By: Relevance
“…A recent Spanish study on university students determined that there is a significant association between adherence to the MD and both a high level of muscular fitness and high level of cardiorespiratory fitness [28]. Furthermore, two studies conducted on schoolchildren found that subjects who were more physically active also had a higher adherence to the MD [26,27]. The biggest difference of the present study from the aforementioned ones is the studied population.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…A recent Spanish study on university students determined that there is a significant association between adherence to the MD and both a high level of muscular fitness and high level of cardiorespiratory fitness [28]. Furthermore, two studies conducted on schoolchildren found that subjects who were more physically active also had a higher adherence to the MD [26,27]. The biggest difference of the present study from the aforementioned ones is the studied population.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies have shown that the level of fitness is significantly associated with the adherence to the MD [24,[26][27][28]. A recent Spanish study on university students determined that there is a significant association between adherence to the MD and both a high level of muscular fitness and high level of cardiorespiratory fitness [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the combined effect of a healthy diet and PA patterns on individuals’ weight status is known [ 76 ], there is no clear evidence that PA may have had a role in our results on vegetarian’s weight profile, as omnivorous, vegetarian, and vegan participants in this study showed similar habits in sports activities. Regarding healthy dietary patterns, the current Health Behavior of School-Aged Children (HBSC) reports indicate that a considerable number of children and adolescents consume insufficient nutrient-rich foods (e.g., 48% of adolescents neither eat fruits nor vegetables; daily consumption of fruits and vegetables are only 60% and 62%, respectively), which results in the failure of most children and adolescents to meet the healthy nutritional recommendations [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 60%
“…This cultural dietary pattern is associated with a reduced weight and a lower abdominal adiposity, with a beneficial effect on anthropometric parameters and cardiometabolic risk factors [235].…”
Section: Dietary Patterns Mediterranean Dietmentioning
confidence: 98%